Strategic and management thinking: An examining of sustainable energy management - Adıgüzel, Zafer (Springer Science and Business Media Deutschland GmbH, 2021)
In general, energy management has emerged as a vital concept to not only address the increasingly serious energy problems but to reduce the consumption, cost, and environmental impact of scarce and valuable energy resources. Because energy is a cost element for both states and companies, the importance of energy management stems from the global need for energy savings at all scales. Among the objectives of energy management are to conserve resources and cost savings while reducing environmental impacts and providing uninterrupted access for energy users. However, with the adoption of a strategically sustainable management approach, together with energy management, future-oriented investments are needed. In the study, energy, strategy and sustainability concepts are examined.
Keywords: Energy Management; Examining of Sustainable; Strategic and Management